THEORETICAL FOUNDATIONS OF FIDUCIARY DUTIES IN COMMON LAW CORPORATE GOVERNANCE - Umarova Kholiskhon Nomoz kizi (Modern American Journals, 2026)
The concept of the modern corporation governed by a board of directors emerged within the framework of the common law legal tradition that developed after the Anglo-Saxon period. At that historical stage, corporate entities in the form understood today did not yet exist within the Anglo-Saxon legal order. Nevertheless, the contemporary understanding of corporate directors can be traced back to the early notion of a trustee or trusted representative operating in that period.
Keywords: Corporate governance, fiduciary duties, common law legal system, board of directors, duty of loyalty, duty of care, duty of disclosure, conflict of interest.